Emotionally charged or politically rational? The preferences of digital users for the presidential candidates - Ratu, Aurelius; Nisrina, Rumaysha Gikha; Setyaningsih, Yuni (Jurnal Kajian Komunikasi, 2025)
Background: YouTube’s impact on shaping voters’s preferences during Indonesian presidential candidates is undeniably significant. As the second-most-used platform, its presence has transformed the communication model into a participatory one. However, as in any democratic climate, are these preferences driven by rational considerations or purely emotional factors? Objective: We explored how user comments on YouTube contribute to the construction of presidential candidate representation. We focused on the main framework, digital discourses, and shift patterns of digital user engagement between July and August 2023. Methods: We used qualitative content analysis and encoded comments from 20 political videos related to Ganjar, Prabowo, and Anies into eleven thematic categories. These categories are then analyzed through frequency mapping, word visualization (wordcloud), and cluster analysis. Results: We found that attributes related to intelligence, leadership, and change were consistently emphasized by digital users. The candidates who are perceived to be cognitively capable and reform-oriented were preferred by digital users. Meanwhile, problems related to corruption and race (SARA) remain, although they have decreased. We found that emotionally charged framing discourses, which in previous periods had proven effective in mobilizing political support, are now showing a decline in appeal, particularly among active digital users who tend to judge leadership in a more rational manner. Conclusion: We argue that YouTube serves as a participatory political landscape where user comments actively reshape the representation of candidates. This clearly challenges traditional charismatic authority and shows a shift in public expectations towards a rational-legal leadership. Implications: Given the tendency for political legitimacy to be determined by media logic, the candidates’s representations must take into account the public’s interests. This situation underscores a change in expectations of political legitimacy. It should remind us that people discuss non-media issues through media: social, economic, and political.